2021
DOI: 10.23939/mmc2021.03.560
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting economic result of business logic improvements using Game Theory for modeling user scenarios

Abstract: A new approach to user behavior modeling based on Game Theory was proposed. It was developed to consider initial intensity, a strategy applied, a profit gained, and resources utilized as inalienable attributes of users' behavior. The approach covers various aspects of users' motivation and rational actions, not only a statistical image of a pool's summary. Additionally, the given model is strongly connected to profit and loss parameters by operating with profit and utilized resources as parts of model input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…If in the conducted series of tests quite good results are obtained from the point of view of real values, then it can be concluded that in similar situations the model ( 6) can be used, although there is no guarantee that a situation will not be encountered when this model turns out to be completely unsuitable. This approach is used very limitedly and only in relatively well-established processes, the performance indicator of which has minimal deviations [2].…”
Section: The Purpose and Methodology Of The Researchmentioning
confidence: 99%
“…If in the conducted series of tests quite good results are obtained from the point of view of real values, then it can be concluded that in similar situations the model ( 6) can be used, although there is no guarantee that a situation will not be encountered when this model turns out to be completely unsuitable. This approach is used very limitedly and only in relatively well-established processes, the performance indicator of which has minimal deviations [2].…”
Section: The Purpose and Methodology Of The Researchmentioning
confidence: 99%